公共服务提供、绩效测评与政府信任:2013连氏公共管理会议综述 = Public service delivery, performance evaluation, and government trust : a review of the 2013 lien conference on public administration - 马亮 Ma, Liang (2015)
提供优质公共服务是政府基本职能。随着政治、社会、经济的发展和科技的进步,人们对政府公共服务提供的能力和质量提出了越来越高的要求;但是另一方面,在全球经济低速与财政紧缩的背景下,政府的财力和人力又捉襟见肘。如何适应新形势的需要,进行技术创新和制度创新,不断提升政府自身能力与提高公共服务的质量和效益,是世界各国政府面临的重大挑战之一。紧紧围绕这一公共管理理论研究和实践的热点,以"国际视角下的公共服务提供与测评"为主题,新加坡南洋理工大学公共管理研究生院于2013年11月15-16日在新加坡召开了"2013连氏公共管理国际会议"。来自18个国家和地区的与会专家学者围绕公共服务提供的创新与改革、比较公共服务提供、公共服务绩效测量与管理、公众参与与公共服务满意度、公共服务合作与治理、公共服务的社会影响等议题展开热烈讨论。会上进行的主题演讲和宣读的论文在一定程度上能代表相关研究领域的最新研究成果和发展。本文对这些演讲和论文进行综述,以凝练和体现该领域的主要研究发现和进展,并勾勒未来研究议程。It is the fundamental role of government to deliver quality public services.In the background of global economic recession and financial austerity, how to innovatively deliver quality public services has increasingly been one of the top priorities of governments across the world. In line with the demand, 2013 Lien Conference on Public Administration held on November 15-16 at Nanyang Technological University,Singapore, was themed "Public Service Delivery and Evaluation." Leading scholars and experts from 18 countries and regions gathered in the Conference and extensively discussed the issues such as public service delivery initiatives and innovations, comparative public service delivery, public service collaboration and governance, and social impact of public service. This article reviews their ideas and viewpoints, summarizes the mainstream research findings and suggests future research agenda in the field.